The Big Bad Wolf - Patterson, James (Alex Cross series, 2004)
At the outset of his career with the FBI, Alex Cross is instructed to track down a band of kidnappers who are snatching people and possibly selling them into slavery, a case that is complicated by a terrible threat to Cross's own family.